Porous composite board for solid oxide electrolytic cell pressure burning
By using zirconia-toughened alumina (ZTA) ceramics and yttria-stabilized zirconia (8YSZ) to prepare porous composite plates, the problems of warping and electrolyte surface scratches during the sintering process of solid oxide electrolytic cell half cells are solved, achieving Improved sintering flatness and thermal shock resistance.
Patent Information
- Application Number
- CN202411549442.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
Smart Images

Figure CN119349998A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sintering porous composite ceramic plates, in particular to a porous composite plate used for press sintering of a solid oxide electrolytic cell. Background Art
[0002] Solid oxide electrolysis cell SOEC uses solid oxide as an electrolytic cell to convert raw material H2O(g) into H2 and O2 through electrochemical reaction at high temperature. SOEC water electrolysis hydrogen production technology can use nuclear energy or renewable energy as an energy source, which can not only achieve efficient and clean large-scale production of H2, but also effectively absorb surplus electricity from renewable energy such as wind power, photovoltaics, and hydropower, meet the future large-scale energy storage needs, and has great development prospects.
[0003] The common planar solid oxide half-cell is composed of three layers of electrolyte, functional layer and support. The above three-layer structure is formed by the co-firing of three materials: 8YSZ electrolyte, 8Y-NiO functional layer and 3Y-NiO support. Due to the different properties and thicknesses of the three layers of materials, there are differences in the shrinkage of the three layers when sintered at high temperatures, causing the fired half-cell to warp. In order to ensure the subsequent quality of the battery stack assembly, it is usually necessary to add additional shaping processes to adjust the flatness of the half-cell, but this method will increase the production cost. Therefore, before the half-cell is sintered, adding a flat plate weight to the surface of the half-cell green electrolyte can effectively improve the sintering warping phenomenon and improve the flatness of the sintered half-cell. It is a common solution to the warping of the half-cell.
[0004] The sintering temperature of the half-cell is generally around 1400°C, so the cover plate during press firing needs to maintain a high strength at up to 1400°C to ensure that the half-cell is flattened. In addition, since the half-cell green body contains a large amount of organic components, as the temperature rises during the sintering process, it will escape and volatilize from the inside of the half-cell. If the organic matter cannot be smoothly volatilized from the inside, it will cause the half-cell to crack. Therefore, the cover plate for press firing of the half-cell needs to have a certain uniform porosity to ensure that the organic gas is smoothly discharged. Finally, the upper surface electrolyte layer is under pressure when the half-cell is press fired. As the temperature rises during the sintering process, the inside of the half-cell will shrink to a certain extent. It is required that the material on the surface of the cover plate does not react with the electrolyte and the surface is smooth and flat, and will not cause scratches on the electrolyte surface.
[0005] Zirconia has good temperature resistance and can maintain good strength above 1400°C. Existing half-cell pressure plates are mostly made of zirconium oxide powder. This type of zirconium plate is generally made of powder with a larger particle size, and has a relatively rough surface, which is easy to scratch the electrolyte surface. In addition, a single zirconium oxide will undergo a transformation from monoclinic to tetragonal at 1200 degrees Celsius. This process is accompanied by a large volume expansion, which poses a greater risk of damage to the pressurized electrolyte surface. In addition, after the tetragonal zirconium oxide at high temperature is cooled to 1200°C, it will transform back into the monoclinic phase. After repeated heating and cooling, the zirconium oxide plate will fracture and fail due to repeated volume contraction and expansion. To solve this problem, Chinese patent CN 104183860 A proposes a process of screen printing 3YSZ on the surface of a commercially available porous zirconia plate to reduce the surface roughness of the zirconium plate and improve the sintering effect. However, since the 3YSZ coating on the surface of this solution is relatively thin, there are problems such as: first, the printed surface roughness is still relatively high, which poses a risk of damaging the electrolyte; second, the surface of the zirconium plate is poorly bonded to the 3YSZ, and the 3YSZ layer is easily detached after multiple thermal cycles, and the thermal shock resistance is poor.
[0006] After research by our research group, we believe that: First, zirconia toughened alumina ZTA ceramics have good mechanical properties and good temperature resistance. Its sintering temperature is above 1600℃, and it can still maintain high strength at 1400℃, which can achieve the effect of applying external force to its surface during half-cell sintering; second, the surface of the green body manufactured by the cast molding process is smooth, which can be used to prepare thinner samples with good thickness uniformity. The prepared composite cover plate original sheet can ensure a smooth surface and uniform size distribution, and can avoid scratches during the press-sintering process. At the same time, when the half-cell is sintered, the internal organic components will be discharged as the temperature rises. Therefore, the interior of the ZTA plate must have a high open porosity to facilitate the exhaust of the sintered half-cell.
[0007] Therefore, it is of great significance to develop a porous composite plate for press sintering of solid oxide electrolytic cells. Summary of the invention
[0008] The task of the present invention is to overcome the shortcomings of the prior art and provide a porous composite plate for press sintering of a solid oxide electrolytic cell, which can not only increase the flat plate pressure on the surface of the half-cell green electrolyte, but also effectively improve the sintering warping phenomenon and improve the flatness of the sintered half-cell.
[0009] The task of the present invention is accomplished by the following technical solutions:
[0010] The porous composite plate used for solid oxide electrolytic cell press sintering adopts ZTA with good temperature resistance and high strength as the base material, and the corresponding original sheet is formed by the casting method. The cover plate and the half-cell contact layer are yttria-stabilized zirconium oxide 8YSZ. The composite plate has a multi-level pore structure, and the warm isostatic pressing process is used to press the stacked layers into a whole. The specific process steps and conditions are as follows:
[0011] (1a) preparing ZTA mixed powder by mixing alumina powder and zirconium oxide powder in a ratio of 20-30% of zirconium oxide to alumina, wherein the powder has a D50 of 800 nm, a particle size distribution of D10=200 nm, and a D90 of 1300 nm;
[0012] (1b) preparing ZTA porous slurry, mixing ZTA mixed powder with binder, dispersant, solvent, pore former and sintering aid in a certain proportion, adding the mixture to a ball mill and stirring evenly;
[0013] (1c) Preparation of ZTA porous green body: degassing the prepared ZTA porous slurry, controlling the viscosity at 20000±1000cps, and then casting the ZTA green body using a tape casting machine, with the thickness controlled at 1.5±0.1mm;
[0014] (2a) preparing 8YSZ porous slurry, mixing 8YSZ powder with a binder, a dispersant, a solvent and a pore-forming agent in a certain proportion, and then adding the mixture to a ball mill and stirring evenly;
[0015] (2b) Preparation of 8YSZ porous green body: degassing the prepared 8YSZ porous slurry, controlling the viscosity at 2500±100cps, and then casting using a tape casting machine with a thickness controlled at 0.3-0.5mm;
[0016] (3) Porous plate pressing: select the cast ZTA porous green sheet and 8YSZ green sheet, and dry the solvent residue to less than 0.2%. Stack one 8YSZ green sheet and three ZTA green sheets from bottom to top. After stacking, use an isostatic press to press them. The pressing temperature is 50-70 degrees and the pressure is 50-80 MPa. Keep pressing for about 40-60 minutes.
[0017] (4) Sintering: The pressed porous plate is placed in a sintering furnace for sintering at a temperature of 1550°C for 6 hours. During the sintering process, the plates are kept at 250°C, 400°C, and 700°C for 3 hours respectively. The heating rate before 700°C is 0.3°C / min, and the heating rate above 700°C is 3°C / min.
[0018] Compared with the prior art, the present invention has the following advantages or effects:
[0019] Because the ZTA original sheet with certain strength and smooth debinding is used as the porous composite plate, the sintering warping of the solid oxide battery can be effectively suppressed and smooth debinding can be ensured, ensuring that a better shaping effect is provided during the half-cell pressing process; at the same time, since the 3YSZ surface layer prepared by the casting method and the multi-level porous ZTA composite layer are isostatically pressed and sintered to form a smooth electrolyte layer, the electrolyte surface is not scratched, ensuring that the prepared cover plate surface is smooth and flat, and the pressure is uniform during pressing and will not scratch the surface of the half-cell; in addition, since the contact layer between the cover plate and the half-cell is yttria-stabilized zirconia (8YSZ), the deformation caused by the phase transition of zirconia when sintering to 1200°C can be avoided to scratch the electrolyte layer of the half-cell, and impurities can be reduced to contaminate the electrolyte surface; in addition, when ZTA is sintered, a small amount of sintering aid is introduced into the ZTA layer to adjust the consistency of the thermal expansion coefficients of ZTA and 8YSZ, reduce the warping during firing, and avoid interlayer peeling during subsequent pressing. In addition, due to the use of warm isostatic pressing molding process, the cast original sheet is subjected to warm isostatic pressing, which makes the cast original sheet stacked and pressed into a whole, so it is not easy to form peeling of each layer during the pressing and firing process, and the thermal shock resistance is better.
[0020] The ZTA mentioned in the application documents stands for ZrO2 toughened Al2O3, which means zirconium oxide toughened alumina ceramics; 8YSZ stands for 8% (molar fraction) Y2O3 Stabilized ZrO2, which means 8% molar fraction yttria stabilized zirconia; 3YSZ stands for 3% (molar fraction) Y2O3 Stabilized ZrO2)SOEC, which means 3% molar fraction yttria stabilized zirconia; SOEC stands for Solid Oxide Electrolysis Cells; % stands for mass percentage or quantity percentage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of a technical route for manufacturing a porous composite plate for press-sintering of a solid oxide electrolytic cell proposed in the present invention.
[0022] Figure 2 Schematic diagram of press sintering of porous composite board.
[0023] Figure 3 It is a schematic diagram of the cross section of a porous composite plate.
[0024] Figure 4 It is a schematic diagram of the stacking of porous composite plates.
[0025] Figure 5 It is a schematic diagram of multi-layer pressing and sintering of porous composite panels.
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings. DETAILED DESCRIPTION
[0027] like Figures 1 to 5 As shown, the porous composite plate used for press-sintering of solid oxide electrolytic cells adopts ZTA with good temperature resistance and high strength as the matrix material to solve the problems of sintering warping and sintering half-cell flatness. The corresponding original sheet is formed by tape casting. The cover plate and the half-cell contact layer are yttria-stabilized zirconium oxide 8YSZ. The composite plate has a porous structure. The warm isostatic pressing process is used to press the stacked layers into a whole. The specific process steps and conditions are as follows:
[0028] (1a) preparing ZTA mixed powder by mixing alumina powder and zirconium oxide powder in a ratio of 20-30% of zirconium oxide to alumina, the powder having a D50 of 800 nm, a particle size distribution of D10=200 nm, and a D90 of 1300 nm;
[0029] (1b) preparing ZTA porous slurry, mixing ZTA mixed powder with binder, dispersant, solvent, pore former and sintering aid in a certain proportion, adding the mixture to a ball mill and stirring evenly;
[0030] (1c) Preparation of ZTA porous green body: degassing the prepared ZTA porous slurry, controlling the viscosity at 20000±1000cps, and then casting the ZTA green body using a tape casting machine, with the thickness controlled at 1.5±0.1mm;
[0031] (2a) preparing 8YSZ porous slurry, mixing 8YSZ powder with a binder, a dispersant, a solvent and a pore-forming agent in a certain proportion, and then adding the mixture to a ball mill and stirring evenly;
[0032] (2b) Preparation of 8YSZ porous green body: degassing the prepared 8YSZ porous slurry, controlling the viscosity at 2500±100cps, and then casting using a tape casting machine with a thickness controlled at 0.3-0.5mm;
[0033] (3) Porous plate pressing: select the cast ZTA porous green sheet and 8YSZ green sheet, and dry the solvent residue to less than 0.2%. Stack one 8Y green sheet and three ZTA green sheets from bottom to top. After stacking, use an isostatic press to press them. The pressing temperature is 50-70 degrees and the pressure is 50-80 MPa. Keep pressing for about 40-60 minutes.
[0034] (4) Sintering: The pressed porous plate is placed in a sintering furnace for sintering at a temperature of 1550°C for 6 hours. During the sintering process, the plates are kept at 250°C, 400°C, and 700°C for 3 hours respectively. The heating rate before 700°C is 0.3°C / min, and the heating rate above 700°C is 3°C / min.
[0035] The structure of the three-dimensional composite lithium alloy material of the present invention is further:
[0036] The adhesive in step (1b) is any one or two of PVA, PVB, methyl cellulose, polyvinyl acetate, paraffin, and hydroxypropyl cellulose, with a ratio of 5-10%.
[0037] The dispersant in step (1b) is any one or two of sodium metasilicate, sodium pyrophosphate, sodium aluminate, fish oil, polyacrylamide, and polyethyleneimine, with a ratio of 3-8%.
[0038] The solvent in step (1b) is water, xylene or ethanol.
[0039] The pore-forming agent in step (1b) is any one or two of soluble starch, urea, ammonium carbonate and graphite, with a ratio of 30%.
[0040] The sintering aids in step (1b) are calcium carbonate and silicon dioxide, and the addition ratios are 3% and 1% respectively.
[0041] The adhesive in step (2a) is any one or two of PVA, PVB, methyl cellulose, polyvinyl acetate, paraffin, and hydroxypropyl cellulose, with a ratio of 5-10%.
[0042] The dispersant in step (2a) is any one or two of sodium metasilicate, sodium pyrophosphate, sodium aluminate, fish oil, polyacrylamide, and polyethyleneimine, with a ratio of 3-8%.
[0043] The solvent in step (2a) is water, xylene or ethanol.
[0044] The pore-forming agent in step (2a) is any one or two of soluble starch, urea, ammonium carbonate and graphite, with a ratio of 30%.
[0045] In industrial application, ZTA mixed powder is prepared: alumina powder and zirconium oxide powder are mixed in a certain proportion, the proportion of zirconium oxide to alumina is 20%-30%, the powder D50 is 800nm, and its particle distribution is D10=200nm; D90=1300nm; ZTA porous slurry is prepared: ZTA mixed powder, adhesive, dispersant, solvent, pore-forming agent, sintering aid are mixed in a certain proportion and added to the ball mill for uniform stirring; the adhesive is one or two of PVA, PVB, methyl cellulose, polyvinyl acetate, paraffin, hydroxypropyl cellulose, and the adhesive ratio is 5%-10%; the dispersant is sodium metasilicate, sodium pyrophosphate, sodium aluminate, fish oil, polypropylene One or two of amide and polyethyleneimine, the dispersant ratio is 3%-8%; the solvent is water or xylene or ethanol; the pore-forming agent is one or two of soluble starch, urea, ammonium carbonate, and graphite, the pore-forming agent ratio is 30%; the sintering aids used are calcium carbonate and silicon dioxide, the addition ratios are 3% and 1% respectively; prepare 8YSZ porous slurry: 8YSZ powder, adhesive, dispersant, solvent, pore-forming agent, mix them in a certain proportion, add them to the ball mill and stir them evenly; the adhesive here is one or two of PVA, PVB, methyl cellulose, polyvinyl acetate, paraffin, hydroxypropyl cellulose, the adhesive ratio is 5%-10%; the dispersant is sodium metasilicate, sodium pyrophosphate, sodium aluminate, fish One or two of oil, polyacrylamide, polyethyleneimine, the dispersant ratio is 3%-8%; the solvent is water or xylene or ethanol; the pore-forming agent is one or two of soluble starch, urea, ammonium carbonate, graphite, the pore-forming agent ratio is 30%; ZTA porous green body preparation: the prepared ZTA porous slurry is degassed, the viscosity is controlled at 20000±1000cps, and then the ZTA green body is cast by a casting machine, and the thickness is controlled at 1.5±0.1mm; 8YSZ porous green body preparation: the prepared 8YSZ porous slurry is degassed, the viscosity is controlled at 2500±100cps, and then the casting machine is used for casting, and the thickness is controlled at 0.3-0.5mm; porous plate pressing: Select the cast ZTA porous green sheet slices into 170×170mm green sheets and 8YSZ green sheets, dry them to ensure that the solvent residue is less than 0.2%, and stack them from bottom to top with 1 8Y green sheet and 3 ZTA green sheets respectively. After stacking, use an isostatic press to press them. The pressing temperature is 50-70 degrees, the pressure is 50-80MPa, and the pressing is maintained for about 40-60 minutes; sintering: put the pressed porous plate into a sintering furnace for sintering. The sintering temperature is 1550℃ for 6h, and the sintering process is kept at 250℃, 400℃, and 700℃ for 3h respectively during the sintering process. The heating rate is 0.3℃ / min before 700℃, and the heating rate is 3℃ / min above 700℃.
[0046] Example 1
[0047] Preparation of ZTA powder: Select alumina powder with a particle size range of 0.2 microns to 1.3 microns and zirconium oxide powder with a particle size range of 0.09 microns to 0.9 microns, place them in a ball mill and mix them evenly, the purity is above 99.9%, and zirconium oxide accounts for 20% of the ZTA powder; Preparation of ZTA slurry: Mix the prepared ZTA powder, solvent, dispersant, pore former, adhesive and sintering aid in a certain proportion, the solvent is a mixture of xylene and anhydrous ethanol, the ratio of the two is 1:1, the dispersant is fish oil, the pore former is soluble starch, the adhesive is polyvinyl butyral, the ratio of ZTA powder, solvent, dispersant and adhesive is: 100:50:8, the amount of pore former used is 30% of the ZTA powder, the sintering aid is calcium carbonate and dimethylbenzene Silicon oxide, the addition ratio is 3% and 1% of the weight of the ZTA mixed powder respectively, and then the mixed solution is ball-milled for 24 hours; prepare 8YSZ slurry: 8YSZ powder, solvent, dispersant, pore-forming agent and adhesive are mixed in a certain proportion, the solvent is a mixture of xylene and anhydrous ethanol, the ratio of the two is 1:1, and 3YSZ powder with a particle size range of 0.2-0.8 microns is selected as the raw material, the dispersant is fish oil, the pore-forming agent is soluble starch, and the adhesive is polyvinyl butyral (PVB). The ratio of 8YSZ, solvent, dispersant, pore-forming agent and adhesive is: 100:100:4:30:8, and then the mixed solution is ball-milled for 24 hours; prepare ZTA porous green body: place the prepared ZTA slurry in a degassing machine for degassing, Control the degassing viscosity to 20000±1000cps, then cast at a casting speed of 0.3m / min, and dry the green body in three temperature zones, the temperatures of which are 60°C, 80°C, and 100°C, respectively, and control the thickness after casting to 1.5±0.1mm; Preparation of 8YSZ porous green body: Degas the prepared 8YSZ porous slurry, control the viscosity at 2500±100cps, and then cast using a casting machine at a casting speed of 0.5m / min. Dry the green body in three temperature zones, the temperatures of which are 30°C, 40°C, and 50°C, respectively, and the thickness is controlled at 0.3-0.5mm; Porous plate pressing: Select the green body with a cast ZTA porous green body slice of 170×170mm, 8YSZ green body, and dry it. Ensure that the solvent residue is less than 0.2%, and stack 1 8Y green sheet and 3 ZTA green sheets from bottom to top. After stacking, use an isostatic press to press at 65°C, pressure 70MPa, and keep pressing for about 60 minutes; Sintering: put the pressed porous plate into a sintering furnace for sintering, first heat to 250°C at a rate of 1°C / min, keep warm for 240 minutes, then heat to 400°C at 1°C / min, keep warm for 120 minutes, then heat to 700°C at 1°C / min, keep warm for 240 minutes, then heat to 1000°C at a rate of 3°C / min, keep warm for 120 minutes, then heat to 1500 degrees Celsius at 3°C / min, keep warm for 300 minutes, and then cool to room temperature with the furnace.
[0048] Example 2
[0049] Preparation of ZTA powder: Select alumina powder with a particle size range of 0.2 microns to 1.3 microns and zirconium oxide powder with a particle size range of 0.09 microns to 0.9 microns, place them in a ball mill and mix them evenly. The purity is above 99.9%, and zirconium oxide accounts for 20% of the ZTA powder; Preparation of ZTA slurry: Mix the prepared ZTA powder, solvent, dispersant, pore-forming agent, adhesive and sintering aid in a certain proportion. The solvent is a mixture of xylene and anhydrous ethanol in a ratio of 1:1. The dispersant is fish oil, the pore-forming agent is soluble starch, the adhesive is polyvinyl butyral, ZTA powder, solvent The ratio of the agent, dispersant and adhesive is 100:50:8, the amount of the pore-forming agent used is 30% of the ZTA powder, the sintering aids are calcium carbonate and silicon dioxide, and the addition ratio is 3% and 1% of the weight of the ZTA mixed powder respectively, and then the mixed solution is ball-milled for 24 hours; prepare 8YSZ slurry: 8YSZ powder, solvent, dispersant, pore-forming agent and adhesive are mixed in a certain proportion, the solvent is a mixture of xylene and anhydrous ethanol, the ratio of the two is 1:1, 3YSZ powder with a particle size range of 0.2-0.8 microns is selected as the raw material, the dispersant is fish oil, the pore-forming agent is soluble starch, and the adhesive is The ratio of 8YSZ, solvent, dispersant, pore former and adhesive is 100:100:4:30:8, and then the mixed solution is ball-milled for 24 hours; preparation of ZTA porous green body: the prepared ZTA slurry is placed in a degassing machine for degassing, and the degassing viscosity is controlled to be 20000±1000cps, and then the casting is carried out, and the casting speed is 0.3m / min. The green body is dried in three temperature zones, and the temperatures of the three temperature zones are: 60℃, 80℃, and 100℃, respectively, and the thickness after casting is controlled to be 0.7±0.1mm; preparation of 8YSZ ... The good 8YSZ porous slurry is degassed and the viscosity is controlled at 2500±100cps. It is then cast using a casting machine with a casting speed of 0.5m / min. The green body is dried in three temperature zones, with temperatures of 30°C, 40°C, and 50°C, and the thickness is controlled at 0.3-0.5mm. Porous plate pressing: the cast ZTA porous green body slices are 170×170mm green bodies and 8YSZ green bodies. They are dried to ensure that the solvent residue is less than 0.2%. From bottom to top, they are stacked with 1 8Y green body, 3 ZTA sheets, and 1 8Y green body. The stacking diagram is shown in the figure below.After stacking, use an isostatic press to press at a pressing temperature of 65°C and a pressure of 70MPa, and keep pressing for about 60 minutes; sintering: put the pressed porous plate into a sintering furnace for sintering, first heat it to 250°C at a rate of 1°C / min, keep it warm for 240 minutes, then heat it to 400°C at a rate of 1°C / min, keep it warm for 120 minutes, then heat it to 700°C at a rate of 1°C / min, keep it warm for 240 minutes, then heat it to 1000°C at a rate of 3°C / min, keep it warm for 120 minutes, then heat it to 1500 degrees Celsius at a rate of 3°C / min, keep it warm for 300 minutes, and then cool it to room temperature with the furnace.
[0050] This embodiment provides a half-cell multilayer pressing scheme, by adding a layer of 8YSZ on the upper cover plate to block the ZTA layer from contacting the upper half-cell, thus protecting the half-cell. As described above, the present invention can be better implemented. The above embodiment is only the best implementation of the present invention, but the implementation of the present invention is not limited to the above embodiment. Other changes, modifications, replacements, combinations, and simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. The porous composite plate used for press sintering of solid oxide electrolytic cells is designed to solve the problems of sintering warping and sintering half-cell flatness. It is characterized by ZTA with good temperature resistance and high strength is used as the matrix material, and the corresponding original sheet is formed by the casting method. The cover plate and the half-cell contact layer are yttria-stabilized zirconium oxide 8YSZ. The composite plate has a multi-level pore structure. The warm isostatic pressing process is used to press the stacked layers into a whole. The specific process steps and conditions are as follows: (1a) preparing ZTA mixed powder by mixing alumina powder and zirconium oxide powder in a ratio of 20-30% of zirconium oxide to alumina, wherein the powder has a D50 of 800 nm, a particle size distribution of D10=200 nm, and a D90 of 1300 nm; (1b) preparing ZTA porous slurry, mixing ZTA mixed powder with binder, dispersant, solvent, pore former and sintering aid in a certain proportion, adding the mixture to a ball mill and stirring evenly; (1c) Preparation of ZTA porous green body: degassing the prepared ZTA porous slurry, controlling the viscosity at 20000±1000cps, and then casting the ZTA green body using a tape casting machine, with the thickness controlled at 1.5±0.1mm; (2a) preparing 8YSZ porous slurry, mixing 8YSZ powder with a binder, a dispersant, a solvent and a pore-forming agent in a certain proportion, and then adding the mixture to a ball mill and stirring evenly; (2b) Preparation of 8YSZ porous green body: degassing the prepared 8YSZ porous slurry, controlling the viscosity at 2500±100cps, and then casting using a tape casting machine with a thickness controlled at 0.3-0.5mm; (3) Porous plate pressing: select the cast ZTA porous green sheet and 8YSZ green sheet, and dry the solvent residue to less than 0.2%. From bottom to top, there are 1 8Y green sheet and 3 ZTA green sheets. After stacking, use an isostatic press to press them together. The pressing temperature is 50-70°C and the pressure is 50-80MPa. Keep pressing for about 40-60 minutes. (4) Sintering: The pressed porous plate is placed in a sintering furnace for sintering at a temperature of 1550°C for 6 hours. During the sintering process, the plates are kept at 250°C, 400°C, and 700°C for 3 hours respectively. The heating rate before 700°C is 0.3°C / min, and the heating rate above 700°C is 3°C / min.
2. The porous composite plate according to claim 1, characterized in that The adhesive in step (1b) is any one or two of PVA, PVB, methyl cellulose, polyvinyl acetate, paraffin, and hydroxypropyl cellulose, with a ratio of 5-10%.
3. The porous composite plate according to claim 1, characterized in that The dispersant in step (1b) is any one or two of sodium metasilicate, sodium pyrophosphate, sodium aluminate, fish oil, polyacrylamide, and polyethyleneimine, with a ratio of 3-8%.
4. The porous composite plate according to claim 1, characterized in that The solvent in step (1b) is water, xylene or ethanol.
5. The porous composite plate according to claim 1, 2, 3 or 4, characterized in that The pore-forming agent in step (1b) is any one or two of soluble starch, urea, ammonium carbonate and graphite, with a ratio of 30%.
6. The porous composite plate according to claim 1, 2, 3 or 4, characterized in that The sintering aids in step (1b) are calcium carbonate and silicon dioxide, and the addition ratios are 3% and 1% respectively.
7. The porous composite plate according to claim 1, characterized in that The adhesive in step (2a) is any one or two of PVA, PVB, methyl cellulose, polyvinyl acetate, paraffin, and hydroxypropyl cellulose, with a ratio of 5-10%.
8. The porous composite plate according to claim 1, characterized in that The dispersant in step (2a) is any one or two of sodium metasilicate, sodium pyrophosphate, sodium aluminate, fish oil, polyacrylamide, and polyethyleneimine, with a ratio of 3-8%.
9. The porous composite plate according to claim 1, characterized in that The solvent in step (2a) is water, xylene or ethanol.
10. The porous composite plate according to claim 1 or 7 or 8 or 9, characterized in that The pore-forming agent in step (2a) is any one or two of soluble starch, urea, ammonium carbonate and graphite, with a ratio of 30%.
Citation Information
Patent Citations
Zirconium oxide plate applied to pressure sintering of plate type anode supporting half SOFC and surface modification method of zirconium oxide plate
CN104183860A
High purity high strength zirconia-alumina-zirconia composite ceramic and preparation method thereof
CN106946574A
Alumina ceramic substrate and preparation method thereof
CN114988854A
Incompletely sintered zirconia ceramic plate and preparation method thereof
CN117263717A
Pressure device for manufacturing solid oxide fuel cell and manufacturing method using the same
KR1020080056967A